2013
DOI: 10.1093/nar/gkt225
|View full text |Cite
|
Sign up to set email alerts
|

Active transcriptomic and proteomic reprogramming in the C. elegans nucleotide excision repair mutant xpa-1

Abstract: Transcription-blocking oxidative DNA damage is believed to contribute to aging and to underlie activation of oxidative stress responses and down-regulation of insulin-like signaling (ILS) in Nucleotide Excision Repair (NER) deficient mice. Here, we present the first quantitative proteomic description of the Caenorhabditis elegans NER-defective xpa-1 mutant and compare the proteome and transcriptome signatures. Both methods indicated activation of oxidative stress responses, which was substantiated biochemicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 67 publications
(72 reference statements)
3
35
3
Order By: Relevance
“…As expected from the near normal phenotype, xpa-1 mutants do not show the extensive transcriptomic modulation seen in segmental progeroid NER-defective mice. However, we, 31,36 and others, 51 identified a small yet informative set of genes differentially expressed in xpa-1 mutants. Gene set enrichment analyses (GSEA) revealed that the biological process (BP) "determination of adult lifespan" was the only overrepresented BP among the regulated genes.…”
Section: Hormesis Maintains Wildtype Phenotypes In Dna Repair Mutantsmentioning
confidence: 66%
See 4 more Smart Citations
“…As expected from the near normal phenotype, xpa-1 mutants do not show the extensive transcriptomic modulation seen in segmental progeroid NER-defective mice. However, we, 31,36 and others, 51 identified a small yet informative set of genes differentially expressed in xpa-1 mutants. Gene set enrichment analyses (GSEA) revealed that the biological process (BP) "determination of adult lifespan" was the only overrepresented BP among the regulated genes.…”
Section: Hormesis Maintains Wildtype Phenotypes In Dna Repair Mutantsmentioning
confidence: 66%
“…Using this strain we could show that NER indeed contributes to repair of oxidative DNA damage in C. elegans as the steady-state levels of the oxidized DNA bases formamidopyrimidines (FapyGua and FapyAde) and 8-hydroxyadenine (8-OH Ade), which are classical BER substrates, are significantly increased in xpa-1 (ok698) mutants. 36 Contradictory reports exist as to whether NER-deficient xpa-1 mutants have shortened lifespan (discussed in ref. 35).…”
Section: Lifespan Of C Elegans Dna Repair Mutantsmentioning
confidence: 99%
See 3 more Smart Citations